Human interface and the management of information : designing information : Thematic Area, HIMI 2020, held as part of the 22nd International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: designing information : Thematic Area, HIMI 2020, held as part of the 22nd International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part I (2020) - Unknown
No abstract available